Evaluating the safety and efficacy of pediatric medications: a comprehensive review of pharmacological interventions in children - Gupta, Khushboo; Kumar Sahu, Kishor (Journal of Neonatal Surgery, 2025)
The physiological and developmental differences between children and adults create special challenges for the safety and effectiveness of medications in pediatric populations. To assess the available data on pharmacological interventions in pediatric care, this review will concentrate on the safety characteristics and therapeutic results of frequently prescribed drugs. We look at pharmacokinetics, clinical research, and drug approval procedures that affect children's medication use, paying special attention to dosage recommendations, side effects, and long-term consequences. Furthermore, we examine the regulatory structures that oversee pediatric drug trials, emphasizing the necessity of more development of formulations and research that is age-appropriate. By giving clinicians, researchers, and policymakers a better understanding of the advantages and disadvantages of pediatric pharmacotherapy, the findings hope to increase the safety and effectiveness of medications for kids.